Performance Enhancement Model of Human Resources through Knowledge Sharing - Arizqi, Arizqi (JDM (Jurnal Dinamika Manajemen), 2017)
This study aims to examine the effect of exogenous variable consisting of organizational dimen-sion including organizational learning culture, support from top management, and individu-als namely openness in communication in affecting knowledge sharing of individuals. Besides, this study also examined how the role of knowledge sharing in improving human resource performance at Sharia Banking. This study was conducted through SEM (Structural Equation Modeling) test by using SmartPLS, a statistical software. The study was done through survey method by distributing questionnaire to 145 employees from frontliner departments at three of Sharia banks in Semarang. The findings of this study showed that two organizational di-mensions (Organizational Learning Culture and Top Management Support) have significant effect on the improvement of knowledge sharing. While Openness in Communication, the individual dimension, could not determine the improvement of knowledge sharing. Then, the improvement of human resource performance at sharia banking could be done by improving knowledge sharing.